The impact of the assimilation of Aquarius sea surface salinity data in the GEOS ocean data assimilation system. Issue 10 (21st October 2014) - Vernieres, G.; Kovach, R.; Keppenne, C.; Akella, S.; Brucker, L.; Dinnat, E.
Abstract Ocean salinity and temperature differences drive thermohaline circulation. These properties also play a key role in the ocean‐atmosphere coupling. With the availability of L‐band space‐borne observations, it becomes possible to provide global scale sea surface salinity (SSS) distribution. This study analyzes globally the along‐track (Level 2) Aquarius SSS retrievals obtained using both passive and active L‐band observations. Aquarius along‐track retrieved SSS are assimilated into the ocean data assimilation component of Version 5 of the Goddard Earth Observing System (GEOS‐5) assimilation and forecast model. We present a methodology to correct the large biases and errors apparent in Version 2.0 of the Aquarius SSS retrieval algorithm and map the observed Aquarius SSS retrieval into the ocean model's bulk salinity in the topmost layer. The impact of the assimilation of the corrected SSS on the salinity analysis is evaluated by comparisons with in situ salinity measurements from Argo. The results show a significant reduction of the global biases and RMS of observations‐minus‐forecast differences at in situ locations. The most striking results are found in the tropics and southern latitudes. Our results highlight the complementary role and problems that arise during the assimilation of salinity information from in situ (Argo) and space‐borne SSS retrievals.